Historical Retrospective of Mediation as an Integrative Concept: Paradigms Studying and Interdisciplinary - Natalya Ivanovna Bashmakova; Natalya Ivanovna Ryzhova; Olga Aleksandrovna Kuznetsova (Управленческое консультирование)
In an article the authors consider relevance of development of the concept «mediation» in the conditions of a multiculturalism and multiparadigmatic character of modern education and need of use of mediation as a special kind of activity of the specialist of a humanitarian profile in modern conditions. Based on the existing scientific and methodological approaches to mediation research as concepts and results of numerous researches, the authors’ definition of the concept «mediation», proceeding from its genesis is offered. The making contents of the concept «mediation» taking into account an interdisciplinary context are revealed, the main paradigms of studying of concept are pointed out and the perspective directions to its use in scientific and methodical researches of features of development of the content of vocational training of specialists of a humanitarian profile are offered.